Uji Validitas Konstruk Pada Instrumen The Binge Eating Scale Dengan Metode Confirmatory Factor Analysis (CFA) - Nadia Audah (UIN Syarif Hidayatullah Jakarta, 2019)
Binge Eating Disorder adalah gangguan makan dimana seorang individu makan secara berlebihan selama periode waktu tertentu karena faktor emosi negatif, namun berbeda dengan bulimia nervosa, individu dengan Binge Eating Disorder tidak memuntahkan kembali makanannya. Binge Eating disorder termasuk eating disorder yang paling sering ditemukan dalam masyarakat. US Census Bureau, International Data Base (2004, dalam Tantiani, 2007) bahwa jumlah penderita Binge Eating Disorder di Indonesia sebesar 1,669,170 dari populasi atau sebesar 218,452,952 orang. Faktor-faktor yang dianggap memengaruhi Binge Eating Disorder adalah perilaku diet, body dissatisfaction, depressive symptoms, modeling of eating disturbance, pressure to be thin, self-esteem, dan social support . Penelitian ini bertujuan untuk menguji validitas kostruk instrumen tersebut. Data dalam penelitian ini diperoleh dari mahasiswa dan mahasiswi Universitas Islam Negeri Syarif Hidayatullah yang berjumlah 280 orang. Metode yang digunakan untuk mengujinya adalah confirmatory factor analysis (CFA) menggunakan software LISREL 8.70. Hasil dari penelitian ini menunjukkan bawa seluruh item yang berjumlah 16 item bersifat unidimensional. Artinya seluruh item hanya mengukur satu faktor saja sehingga model satu faktor yang diteorikan oleh The Binge Eating Scale dapat diterima. Binge Eating Disorder is an eating disorder in which an individual eats excessively over a period of time due to negative emotional factors, but in contrast to bulimia nervosa, individuals with Binge Eating Disorder do not regurgitate their food. Binge Eating disorder includes eating disorders that are most often found in society. US Census Bureau, International Data Base (2004, in Tantiani, 2007) that the number of sufferers of Binge Eating Disorder in Indonesia is 1,669,170 from the population or amounting to 218,452,952 people. Factors that are considered to influence Binge Eating Disorder are dietary behavior, body dissatisfaction, depressive symptoms, modeling of eating disturbances, pressure to be thin, self-esteem, and social support. This study aims to examine the validity of the boarding instrument. The data in this study were obtained from students and students of the Syarif Hidayatullah State Islamic University totaling 280 people. The method used to test it is confirmatory factor analysis (CFA) using LISREL 8.70 software. The results of this study indicate that all 16 items are unidimensional. This means that all items only measure one factor so that the one factor model theorized by The Binge Eating Scale is acceptable.